(3GdGSJbUGA hGdJLfjS aj Yde GdMSGH ESeGYjd Hf jhSa Hf YeQ GdRHjOi GdTGaYi aVd Gddg GdCejQ Gdedc GdYGOd Cs - (3Ydj Hf MQH Hf eMeO GdWGFj GdehUdj, CHh GdMSf,J (B265 (3g` s
(3ChdgG (B:s
(3aVd Gddg GdCejQ Gdedc GdYGOd CJSRNhGQRe TGg s
(3BNQgG (B:s
(3hbO CJjfG Ydi GdWQb GdJi jecf Cf jSJNQL HgG eSGFd GdhUGjG hEf cGfJ CfhGY eSGFdgG s
(3fSNI KGfjI cGdSGHbIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B270 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B57s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B11 s
Keywords: (3GdQjGVjGJs